Organizational renewal capabilities with the framework of Strategic leadership An Analytical comparative Research At some Hospitals in Baghdad - الطائي علي حسون; الكبيسي سندس محسن (Journal of Economics and Administrative Sciences, 2016)
Strategic leadership is the main source to enable organizations of excellence in light of turbulent environment, it is also the capabilities of organizational renewal organization’s ability to anticipate changes that take place or possible occurrence. As a result of the many changes that characterize the environment where they operate researched hospitals, many of them began looking for ways to help it achieve a lot of their own competitive advantages. The subject of organizational renewal capabilities of subjects that are not obvious interest in the Arab environment in general and Iraq in particular, and longer. The problem of the research and field presence of deficiencies in the application of strategic concepts of leadership and interest in achieving renewal Organizational capabilities and its role in the omission of some of the hospitals in Baghdad. Based on this problem, and to clarify the relationship between the main and subsidiary research variables were formulated three hypotheses Head branched reported (10) sub-hypothesis. It distributed to a sample of (86) employees of hospitals administrators and managers and directors of departments and of people and their assistants managers in three hospitals of Baghdad’s hospitals are: "Imam Kadhim Hospital, Karkh Hospital, Adnan" statistical methods has produced a number of results Perhaps the most prominent of which there were no significant correlation between relationship Strategic leadership and organizational renewal capabilities, also it turned out that there is a significant effect between the strategic leadership capabilities and organizational renewal. There are significant differences between the answers Strategic leadership and its dimensions (the development of human capital, and preservation of culture poignant, and emphasis on ethical practices) did not appear in the Dimensions (strategic direction, exploring competencies and maintain) in researched hospitals. There are significant differences in the average answers organizational renewal capacities dimensions (strategic skills, use the time, driving behaviors, communication) did not appear in dimensions (orientation towards learning, knowledge management) in researched hospitals. In the framework of the discussion of the results Search made a number of recommendations, including: the need to pay greater attention to the strategic leadership and considered the key to the evolution of researched hospitals and the development of administrative leadership to be responsive to the requirements of this leadership and provide dimensions where and to disseminate the concept of organizational renewal and considered the biggest challenge facing organizations today of different kinds.